Association of larvae and adults of Mexican species of Macrelmis (Coleoptera: Elmidae): a preliminary analysis using DNA sequences - Curiel, Josefina; Morrone, Juan J. (Zootaxa, 2012)
Insect life stages are known imperfectly in many cases, and classifications are usually based on adult morphology. This isunfortunate as information on other life stages may be useful for biomonitoring. The major impediment to using elmid(Coleoptera) larvae for freshwater biomonitoring is the lack of larval descriptions and illustrations. Reliable molecular proto-cols may be used to associate larvae and adults. After adults of seven species of Mexican Macrelmis were identified morpho-logically, seven larval specimens were associated to them based on two gene fragments: Cox1 and Cob. The phylogeneticanalysis allowed identifying the larval specimens as Macrelmis leonilae, M. scutellaris, M. species 7, M. species 10, and M.species 11. Two species based on adults associated uncertainly with one larva, and one larva did not match with any adult. Adult/larval association in elmids using DNA sequence data seems to be promising in terms of speed and reliability.